A qualitative study of unpaid caregivers of persons living with dementia and their interactions with health and community-based services and providers. (February 2023) - Liebzeit, Daniel; Fields, Beth; Robinson, Erin L; Jaboob, Saida; Ashida, Sato
Background and Objectives: Unpaid caregivers frequently feel underprepared and without adequate training, support, or access to services and resources to care for persons living with dementia. Health and community-based services and providers are critical to support persons living with dementia and their unpaid caregivers. The objective of this research is to understand how unpaid caregivers of persons living with dementia interact with health and community-based services and providers. Research Design and Methods: We used a qualitative descriptive approach to analyze data from one-on-one semi-structured interviews with unpaid caregivers of persons living with dementia ( N = 25). We used framework analysis to organize themes and sub-themes within the systems approach to healthcare delivery. Findings: Participants described a need for additional guidance, information, and support from health and community-based services and providers. This need was described by participants at 4 levels: individual, care team, organization, and political and economic environment. Participants were active in proposing potential solutions to challenges at all 4 levels, including improving provider awareness and training in dementia, opportunities to provide resources and referrals upon dementia diagnosis, a central clearinghouse for information and resources for persons living with dementia and caregivers, and opportunities to close service gaps. Discussion and Implications: Findings of this study highlight the need for increased involvement of caregivers of persons living with dementia as community stakeholders for improving care and services. Recommendations to promote high quality care and better support unpaid caregivers by developing interventions to address multiple aspects of healthcare delivery are consistent with recent legislation and are important areas of future research.